THE ROLE OF ISLAMIC EDUCATION IN REALIZING SOCIAL INTERACTION BASED ON MULTICULTURALISM AMONG STUDENTS OF DIFFERENT RELIGIONS IN ELEMENTARY SCHOOLS - Syamsul Bahri (The Islamic Education and Multiculturalism Foundation, 2019)
this research seeks to reveal the role of Islamic Religious Education (PAI)in realizing multiculturalism-based social interactions in elementary schools.PAI is one lesson in the national curriculum that is taught at each educationalinstitution. Islamic Religious Education is very appropriate to be carried out torealize harmonious social interaction among students of different religions basedon multiculturalism. This research was conducted at Taman HarapanElementary School and Bina Budi Mulia Elementary School Malang City, aprivate school that has multi-ethnic and multi-religious students. The problemsraised in this study are how is the role of PAI in realizing multiculturalism-basedsocial interaction among students of different religions in elementary schools?The research method used is qualitative and the research approach isphenomenology. The Researcher collected data through observation, interviewsand document review. Interviews were conducted with school principals, PAIteachers and students. The research results showed that Taman HarapanElementary School and Bina Budi Mulia Elementary School strongly supportedthe harmonious interaction of students of different religions in the schools. TheConducive social interactions occur in two forms, namely interactions within theclassroom, and social interactions outside the classroom. The social interaction inthe classroom takes place by working together, learning together, discussing andhelping each other. While the interactions outside the school take place inextracurricular activities such as sports, religious holidays, arts performances,outbound, and friendship interactions in the school environment. Keywords: PAI, social interaction, Taman Harapan Elementary School, Bina BudiMulia Elementary School